BIBLIOMETRIC ANALYSIS AND SYSTEMATIC REVIEW FOR THE USE OF GAMIFICATION IN FASHION DESIGN EDUCATION - ARSLAN, Büşra; ÇEĞİNDİR, Neşe Yaşar (SSD Journal, 2024)
Various strategies and methods have been constantly tried in educational environments from past to present. The common purpose of the developed strategies and methods is to make the learning process more effective by keeping the attention and motivation of the learners high. In this context, the main purpose of the study is to analyze the publications on the use of gamification in fashion design education with bibliometric methods and examine them with a systematic review approach. In the first part of the study, in which the descriptive research method was used, the Scopus (Elsevier) database was scanned with the keywords ("gamification" OR "gamify") AND "fashion design" AND "education", and the obtained data were analyzed and evaluated using the bibliometric analysis method. In the second part of the study, 10 publications directly related to the subject, found with the same keywords in the Google Scholar database, were selected and these publications were examined in depth with a systematic review approach. In the analysis, it was determined that gamification was used most commonly in fashion marketing and least in fashion design education. It has been determined that gamification applications in the publications analyzed through systematic review generally yield positive results in line with the targeted purposes, and that the applications need to be developed and expanded, especially in fashion design education, where creativity is intense.